Cult, herding, and ‘pilgrimage’ in the Late Neolithic of north-west Arabia: Excavations at a mustatil east of AlUla - Kennedy, Melissa; Strolin, Laura; McMahon, Jane; Franklin, Daniel; Flavel, Ambika; Noble, Jacqueline; Swift, Lauren; Nassr, Ahmed; Fallon, Stewart; Thomas, Hugh (PLOS ONE, 2023)
Since the 1970s, monumental stone structures now called mustatil have been documented across Saudi Arabia. However, it was not until 2017 that the first intensive and systematic study of this structure type was undertaken, although this study could not determine the precise function of these features. Recent excavations in AlUla have now determined that these structures fulfilled a ritual purpose, with specifically selected elements of both wild and domestic taxa deposited around a betyl. This paper outlines the results of the University of Western Australia’s work at site IDIHA-0008222, a 140 m long mustatil (IDIHA-F-0011081), located 55 km east of AlUla. Work at this site sheds new and important light on the cult, herding and ‘pilgrimage’ in the Late Neolithic of north-west Arabia, with the site revealing one of the earliest chronometrically dated betyls in the Arabian Peninsula and some of the earliest evidence for domestic cattle in northern Arabia.